Design and Implementation Of Blended Learning Approach For Simulation Education Among Undergraduate Nursing Students - et.al, Miran Eom (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The importance of undergraduate nursing education has never been higher due to the aging population and complexity of patients. The blended simulation combined two and more educational methods and is an effective strategy in nursing education. This study was to evaluate the effectiveness of blended simulation using standardized patients and patients simulation. Using a convenience sampling, a quasi-experimental study was conducted. Forty undergraduate nursing students enrolled and were allocated into the experimental group (n=20) or the control group (n=20). CPX (clinical performance examination) was used to evaluate physical assessment skills. Self-reporting questionnaires were used for communication skill and learning satisfaction. χ2-test/Fisher’s exact test and Mann-Whitney U test were conducted for statistical analysis. After completing the educational program, there were statistically significant higher levels of physical assessment and communication skills in the blended simulation group (p<.001) compared with the control group. Regarding learning satisfaction, there were also statistically significant differences with higher level of satisfaction among students in blended simulation group (p=.002). This blended simulation has high potential to successfully achieve learning outcomes in undergraduate nursing education. Providing students diverse educational methods ensures an optimal learning experience.